2022
DOI: 10.3390/biom12040564
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Endocrine Disruptor Exposure on Collagen-Induced Arthritis

Abstract: Endocrine disruptors (EDs) are chemical substances capable of affecting endocrine system functioning and interfering with organ morphogenesis and physiological functions. The development and regeneration of bone tissues have a complex hormonal regulation, and therefore, bone tissue cells can be considered potential targets for endocrine disruptors. In that regard, the aim of this research was to investigate the impact of ED exposure on the inflammatory response and oxidative stress in an experimental model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…It has been shown that 25–33% of diseases are linked to POP exposure. The studies conducted so far showed that prolonged exposure to POPs negatively affected growth, postnatal development, and the endocrine system [ 16 , 17 , 23 ]. Vinclozolin studies are mainly focused on the reproductive system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that 25–33% of diseases are linked to POP exposure. The studies conducted so far showed that prolonged exposure to POPs negatively affected growth, postnatal development, and the endocrine system [ 16 , 17 , 23 ]. Vinclozolin studies are mainly focused on the reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vinclozolin prepubertal exposure in male rats inhibits pubertal maturation and slows the growth of the accessory sex gland and epididymis [ 36 ]. D’Amico and colleagues recently demonstrated that the effect of endocrine disruptor exposure was not limited to the urogenital apparatus [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts from cytosol and nucleus were prepared as previously described and incubated with the antibodies anti-NRF-2 (1–500, SCB, Heidelberg, Germany, #sc-365949), anti-heme oxygenase 1 (HO-1; 1-500, SCB, Heidelberg, Germany, #sc-136960), anti-β-tubulin (1–500, SCB, Heidelberg, Germany, #sc-166729), and anti-MAP2 (1–500, SCB, Heidelberg, Germany, #sc-74421) in 1× PBS, 5% w / v non-fat dried milk and 0.1% Tween-20 at 4 °C overnight [ 46 , 47 , 48 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. For the cytosolic and nuclear fraction, blots were also probed with β-actin and lamin A/C protein to ensure that they were filled with equivalent amounts of proteins (1:500; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis was performed as previously described [ 47 , 48 , 49 ]. Primary antibodies anti-MC chymase (1:100, Santa Cruz Biotechnology (SCB) Heidelberg, Germany, #sc59586) and anti-MC tryptase (1:100, SCB, #sc59587) were incubated overnight on the lung tissue sections.…”
Section: Methodsmentioning
confidence: 99%